The Administrative Contract and Decision in the Light of Controlling Legality and Legal Security - Reffaf, Lakhdar; Achache, Hamza (Journal of Legal Studies and Researches, 2023)
The current study aims at shedding the light on the administrative decision and contract in the light of the principles of legality and legal security. This is done through trying to clarify the necessary previsions and rules to be followed by the administration in order to fulfill the effectiveness of the administrative activity, as well as to maintain a better functioning of the public facility.